Lost and found in music: Music, consciousness and subjectivity. (September 2014) - Clarke, Eric F.
"Strong experiences of music"—to use Alf Gabrielsson's (2011) term—commonly, but apparently paradoxically, seem to involve people in both losing themselves and finding themselves in music. How can this be? Who or what is lost, and, equally, who or what is found, and how can they both happen together? In this paper I offer an approach to these questions, framed within the perspectives of musical consciousness and musical subjectivity, that attempts to bring together perceptual, emotional and embodied components of musical experience, embedded in the ecology of everyday listening. In doing so, I also argue for the importance of paying proper attention to phenomenological qualities of listeners' experiences, for the historically specific and changing nature of human subjectivity experienced through music, and for a dynamic and animated understanding of musical engagement.